2017
DOI: 10.1116/1.4983830
|View full text |Cite
|
Sign up to set email alerts
|

Directional etch of magnetic and noble metals. II. Organic chemical vapor etch

Abstract: Surface oxidation states of transition (Fe and Co) and noble (Pd and Pt) metals were tailored by controlled exposure to O2 plasmas, thereby enabling their removal by specific organic chemistries. Of all organic chemistries studied, formic acid was found to be the most effective in selectively removing the metal oxide layer in both the solution and vapor phase. The etch rates of Fe, Co, Pd, and Pt films, through an alternating plasma oxidation and formic acid vapor reaction process, were determined to be 4.2, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Physical sputtering has limited etch selectivity and cannot obtain the required pattern quality, due to uncontrolled redeposition of non-volatile Ni particles, resulting in sloped sidewalls and Ni residues on the mirror [9]. However, Ni can form volatile organo-metallic compounds at low temperature [34,35], and emerging etch technology, such as atomic layer etch (ALE), can be promising for enabling transitional metal plasma etch [36]. Alternatively, a damascene-like additive patterning scheme can be adopted to circumvent the direct Ni etching [37].…”
Section: Film Morphologymentioning
confidence: 99%
“…Physical sputtering has limited etch selectivity and cannot obtain the required pattern quality, due to uncontrolled redeposition of non-volatile Ni particles, resulting in sloped sidewalls and Ni residues on the mirror [9]. However, Ni can form volatile organo-metallic compounds at low temperature [34,35], and emerging etch technology, such as atomic layer etch (ALE), can be promising for enabling transitional metal plasma etch [36]. Alternatively, a damascene-like additive patterning scheme can be adopted to circumvent the direct Ni etching [37].…”
Section: Film Morphologymentioning
confidence: 99%
“…The recently developed chemical dry etching schemes for cobalt ALE rely on thermal chemistry of cobalt surfaces with diketones, the compounds that have been shown to have high affinity to metals. [5][6][7] A simple acetylacetone (2,4-pentanedione, acacH) and hexafluorinated version of this compound (1,1,1,5,5,5-hexafluoro-2,4,-pentanedione, hfacH) have been used successfully to etch oxidized cobalt surfaces; 8,9 however, it was also shown recently that the proposed volatile product, Co(hfac) 2 , does not form on a clean cobalt surface 10 and that the presence of surface oxygen is required for this product to form. Even when Co(hfac) 2 is formed on the oxidized cobalt surface in a self-limited reaction, it was not observed to desorb until approximately 350°C, 10 the temperature substantially higher than the industrial processing conditions and experimentally observed etching.…”
Section: Introductionmentioning
confidence: 99%
“…94) satisfied. 96) By tuning the oxide thickness generated by O 2 plasma exposure, the etching of metals can be controlled at an atomic level. [95][96][97][98] 2.4 Next steps in atomic layer processing Area-selective deposition is another approach garnering much attention.…”
Section: Atomic Layer Processing Of Multiferroic Materialsmentioning
confidence: 99%
“…Chen et al demonstrated the chemical contrast produced using reactive ion bombardment with the subsequent delivery of vapor-phase organics to the modified surface, resulting in an anisotropic and self-limiting etching process capable of achieving greater selectivity to the underlying metal. 96) A dilemma occurs in self-limiting modifications, and a problem is that stable by-products at room temperature tend to be nonvolatile and vice versa. In brief, the volatilities of the etching by-products are determined by the chemical nature of the bonding when forming the solid phase, which in turn depends on molecular weights, intermolecular forces, and so forth.…”
Section: Future Challengesmentioning
confidence: 99%